Conservação e qualidade da carne de grumatã (Prochilodus lineatus) após diferentes períodos de depuração e armazenamento - (:unkn) unknown (Universidade Federal do Pampa, 2019)
Grumatã (Prochilodus lineatus) is a species of detritivore-iliophage feeding habit. As a result of their bottom feeding, characteristics like flavor and odor of earthy and musty cause off-flavor in the meat. Off-flavor is due to the absorption of the compounds geosmin (GEO) and 2-methylisoborneol (MIB), which can be reduced with an application of the depuration process. Although fish go through this process, fish meat is the most vulnerable to microbial deterioration and lipid oxidation. The objective of this study was to evaluate the bromatological, microbiological, sensorial and meat quality characteristics of P. lineatus after different depuration periods (0 h, 48 h, 72 h and 96 h) and conservation (0, 2, 4 and 6 months storage under freezing). The collection of the specimens was carried out at the dam of the municipality of Uruguaiana - RS, followed by transportation to the Centro de Tecnologia em Pesca e Aquicultura (CTPA) of the Universidade Federal do Pampa (UNIPAMPA) - Campus Uruguaiana. After the arrival of the fish, the distribution was carried out between the different depuration periods: 0 h (without depuration), 48 h, 72 h and 96 h. At the end of each treatment period, the fish were slaughtered, filleted and stored as samples (- 18°C) until analysis. The bromatological results showed higher fat content in the treatment samples 0 and 72 h, with preservation of the muscle protein of the depuried fish; the sensorial analysis revealed no difference between the different treatments; for the evaluation of the samples stored for six months, with analyzes performed every two months, the pH showed increasing values at two months of storage for the 0 h treatment, and at four months of storage for the depuried treatments (48, 72 and 96 h); the Total Volatile Base Nitrogen (BNVT) varied in treatments 48 and 96 h over the shelf life; the peroxides increased from the fourth month of storage and in the sixth month higher values were observed; for Thiobarbituric Acid Reactive Substances (TBARS), the treatment 0 h had more formations of volatile substances, and there were no significant differences in the other treatments (48, 72 and 96 h) during storage. Therefore, we can conclude that the depuried fish present greater efficiency only in relation to the quality of the grumatã meat when stored under freezing over the months.
Conservation and quality of blue-eyed meat (Prochilodus lineatus) after different periods of purification and storage
Keywords: Aquicultura; Oxidação de gorduras; Armazenamento; Off-flavor; Aquaculture; Lipid oxidation; Storage; CNPQ::CIENCIAS AGRARIAS